2016
DOI: 10.1158/0008-5472.can-15-2302
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb Enhances Breast Cancer Invasion and Metastasis through the Wnt/β-Catenin/Axin2 Pathway

Abstract: The molecular underpinnings of aggressive breast cancers remain mainly obscure. Here we demonstrate that activation of the transcription factor c-Myb is required for the prometastatic character of basal breast cancers. An analysis of breast cancer patients led us to identify c-Myb as an activator of Wnt/b-catenin signaling. c-Myb interacted with the intracellular Wnt effector b-catenin and coactivated the Wnt/b-catenin target genes Cyclin D1 and Axin2. Moreover, c-Myb controlled metastasis in an Axin2-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 43 publications
5
70
4
Order By: Relevance
“…Wnt signaling pathway has been reported to be correlated with cancer cell metastasis 25. Our study also demonstrated that MLL1 interacted with β-catenin.…”
Section: Resultssupporting
confidence: 71%
“…Wnt signaling pathway has been reported to be correlated with cancer cell metastasis 25. Our study also demonstrated that MLL1 interacted with β-catenin.…”
Section: Resultssupporting
confidence: 71%
“…Moreover, we revealed that the activity of th Wnt/β-catenin signaling pathway was decreased after Prrx2 silenced by using the luciferas reporter assay system. Cyclin-D1 is one of the important target genes downstream of the Wnt/β-catenisignag pathway [25, 26], silencing of Prrx2 could significantly inhibit the expression of cyclin-D1. The above experiments revealed that Wnt/β-catenin signaling pathway may participate in Prrx2-induced EMT of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental metastasis to the lungs was induced by injecting 0.2 × 10 6 cells in 100 μl of PBS in the tail vein of female athymic nude mice. Mouse nipple implantation of 4T1 cells was based on a previously published method49. Female BALB/c mice were anaesthetized and used for this assay.…”
Section: Methodsmentioning
confidence: 99%